Chemically-Induced DNA Damage, Mutagenesis, and Cancer - Takehiko Nohmi (Ed.); Ashis K. Basu (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Human cancers frequently arise from exposure to chemicals, although radiation, oxidation, and genetic factors play critical roles as well. DNA damage by these agents in a cell is an important first step in the process of carcinogenesis. DNA repair processes have evolved to repair these damages. However, the replication of damaged DNA may occur frequently prior to repair, resulting in gene mutations and the generation of altered proteins. Mutations in an oncogene, a tumor-suppressor gene, or a gene that controls the cell cycle give rise to a clonal cell population with an advantage in proliferation. The complex process of carcinogenesis includes many such events, but has been generally considered to be comprised of the three main stages known as initiation, promotion, and progression, which ultimately give rise to the induction of human cancer. The articles published in this book entitled (3z(BChemically-Induced DNA Damage, Mutagenesis, and Cancer(3y (Bprovide an overview on the topic of the (3z(Bconsequence of DNA damage(3y (Bin the context of human cancer with their challenges and highlights.s
English
Keywords: genotoxicity; chemoprevention; DNA damage; metal toxicity; apoptosis; melanoma; tumor cells; DNA repair; chemotherapy; translesion synthesis